Sustainability index accounting food and carbon benefits on circular 2, 3-butanediol biorefinery with oil palm empty fruit bunches. (1st December 2021) - Rehman, Shazia; Islam, Md Khairul; Khanzada, Noman Khalid; Zhuang, Huichuan; Wang, Huaimin; Chaiprapat, Sumate; Leu, Shao-Yuan
Graphical abstract: Highlights: First sustainability index (7.3) for food (0.5) and carbon (6.8) benefits for biomass biorefinery. 247 kg 2, 3-BDO was produced from 1 tonne empty fruit bunches at a high titer of 77.3 g/L. Staged organosolv pretreatment resulted in 0.988 kgCO2 -eq carbon sequestration per kg biomass. Energy use in biorefinery is 73.3 MJ/kg-BDO or 15.5% lower than conventional refinery. 1.54 kg food crop can be saved by shifting bio-BDO feedstock from 1st to 2nd generation. Abstract: Progressive replacement of petroleum chemicals with biomass derived products is an essential research goal toward sustainability. However, the progress of the development of new generation biorefinery has been affected by many factors, i.e ., prices of crude oil, food, and carbon. To quantify the environmental and social impacts of the technologies, this study constructed a sustainability index for calculating two new bio-butanediol production processes with oil palm empty fruit bunches as example feedstock. The performance of organosolv pretreatment using butanediol was compared with the whole slurry conversion process using sulfite pretreated biomass, over the petroleum refinery and first generation biorefinery with food crop feedstock. The organosolv biorefinery process successfully converted the biomass into 77.3 ± 1.63 g/L of bio-butanediol (0.45 g/g yield), which is slightly higher (5.5%) than that of the sulfite-based process. The integration of biorefinery techniques, with oil palm farming shall result in 6.8 kg-CO2 and 0.5 kg-food benefits per kg butanediol produced, yielding a sustainability index of 7.30. The food index for first generation biorefinery is −1.04 kg food per kg butanediol produced. Using empty fruit bunches for butanediol production could save 1.54 kg food crop consumption, which turns the "food vs. fuel competition" into a "food plus fuel nexus".